Are China's climate commitments in a post‐Paris agreement sufficiently ambitious?. (2nd December 2016) - Zhang, ZhongXiang
Abstract : In international climate change negotiations, China's role is an issue of perennial concern. In particular, the lack of quantitative, absolute emissions commitments from China has often been the focus of this concern. In line with changing domestic and international contexts, China is recalibrating its stance and strategy. Its participation in international climate change negotiations has evolved from playing a peripheral role to gradually moving to the center. This article examines China's stance and role in international climate change negotiations from a historical perspective. In so doing, the article discusses the evolution of international climate negotiations and China's stance in the lead‐up to and at the Paris conference. With Paris behind us, the focus is now turning to the implementation of the Paris Agreement. The article discusses post‐Paris focuses, generally in the international context and in particular in China's context. They both affect the outcomes of post Paris subsequent negotiations and hold the key to actually achieving desired outcomes. WIREs Clim Change 2017, 8:e443. doi: 10.1002/wcc.443 This article is categorized under: Policy and Governance > International Policy Framework Abstract : Comparison of global emission levels in 2025 and 2030 resulting from the implementation of the INDCs and under other scenarios.